Pesantren and Media Imperialism: Resistance Against the Hegemony of Mainstream Media in Constructing the Issue of Radicalism-Terrorism in Indonesia - Abdul Choliq; Muhibbin; Kun Wazis (Fakultas Usluhuddin dan Dakwah UIN Syekh Wasil Kediri, 2025)
The contemporary media landscape has undergone profound transformations in the digital age, fundamentally altering how information is produced, disseminated, and consumed across global societies. This study examines the intersection of media imperialism and Islamic educational institutions (pesantren) in Indonesia, focusing on how these traditional institutions resist hegemonic mainstream media narratives regarding radicalism and terrorism. Through qualitative research methodology employing in-depth interviews and content analysis, this research investigates how pesantren develop counter-narratives and alternative media strategies to challenge dominant discourse. The findings reveal that pesantren employ various forms of media resistance, including the establishment of independent media outlets, strategic use of digital platforms, and community-based communication networks. These institutions demonstrate remarkable adaptability in navigating contemporary media challenges while maintaining their cultural identity and educational mission. The study contributes to understanding media imperialism in the Indonesian context and highlights the agency of religious institutions in contesting hegemonic representations. The research concludes that pesantren’s media resistance strategies serve not only as corrective measures against misrepresentation but also as forms of cultural preservation and democratic participation in public discourse.